Biophysical properties of DNA in hydrated ionic liquids - Jumbri, Khairulazhar; Ahmad, Haslina; Abd. Malek, Emilia; Abdul Rahman, Mohd Basyaruddin (AIP Publishing, 2016)
The biophysical properties and behavior of natural calf thymus DNA in hydrated 1-ethyl-3-butylimidazolium bromide ionic liquid ([C2bim]Br) have been studied using spectroscopy technique. The effect of ionic liquid concentration and temperature towards the duplex B-DNA conformation were determined. The presence of ionic liquid causes higher duplex DNA stability with the DNA melting temperature of ∼56°C without any addition of buffer solutions. The electrostatic attraction between ionic liquid’s cation and DNA phosphates groups was found play a main role in stabilizing native DNA structure. Understanding of the biophysical properties of DNA in this ionic media could be used as a platform for future development of specific solvent for nucleic acid nanotechnology.